CYP3A4∗22 Genotyping in Clinical Practice: Ready for Implementation? - Mulder, Tessa A. M.; van Eerden, Ruben A. G.; de With, Mirjam; Elens, Laure; Hesselink, Dennis A.; Matic, Maja; Bins, Sander; Mathijssen, Ron H. J.; van Schaik, Ron H. N. (Frontiers in Genetics, 2021)
Cytochrome P450 3A4 (CYP3A4) is the most important drug metabolizing enzyme in the liver, responsible for the oxidative metabolism of ∼50% of clinically prescribed drugs. Therefore, genetic variation in CYP3A4 could potentially affect the pharmacokinetics, toxicity and clinical outcome of drug treatment. Thus far, pharmacogenetics for CYP3A4 has not received much attention. However, the recent discovery of the intron 6 single-nucleotide polymorphism (SNP) rs35599367C>T, encoding the CYP3A4*22 allele, led to several studies into the pharmacogenetic effect of CYP3A4*22 on different drugs. This allele has a relatively minor allele frequency of 3-5% and an effect on CYP3A4 enzymatic activity. Thus far, no review summarizing the data published on several drugs is available yet. This article therefore addresses the current knowledge on CYP3A4*22. This information may help in deciding if, and for which drugs, CYP3A4*22 genotype-based dosing could be helpful in improving drug therapy. CYP3A4*22 was shown to significantly influence the pharmacokinetics of several drugs, with currently being most thoroughly investigated tacrolimus, cyclosporine, and statins. Additional studies, focusing on toxicity and clinical outcome, are warranted to demonstrate clinical utility of CYP3A4*22 genotype-based dosing.